Women Learners in Higher Education: Transformational vs. Transactional Leadership Development - Kathryn McAtee; Catherine Hansman; Catherine Monaghan (Adult Education Research Conference, 2008)
The purpose of this research is to gain a greater understanding of how women learn to be leaders in higher educational institutions.
Keywords: women; leadership development; feminist critical theory